Temporal lobe surgery in Germany from 1988 to 2008: diverse trends in etiological subgroups. (7th December 2013) - Helmstaedter, C.; May, T. W.; von, M.; Pfaefflin, M.; Ebner, A.; Pannek, H. W.; Elger, C. E.; Stefan, H.; Schramm, J.
<x xml:space="preserve">Abstract</x> Background and purpose In the epilepsy community, there is talk that the number of classical patients with early onset temporal lobe epilepsy (TLE) and Ammon's horn sclerosis (AHS) is decreasing. This is counterintuitive, considering the success story of epilepsy surgery, improved diagnostic methods and the current recommendation of early admission to surgery. In order to recognize trends, the development of temporal lobe surgery over 20 years in three major German epilepsy centers was reviewed. Methods Age at surgery and duration of epilepsy, which was differentiated according to histopathology (AHS, developmental, tumor, vascular), year of surgery and center, were evaluated in a cohort of 2812 patients from three German epilepsy centers who underwent temporal lobe surgery between 1988 and 2008. The analysis was carried out for the pooled cohort as well as for each center separately. Results Of all patients, 52% showed AHS. Compared with other pathologies, the AHS group had the earliest epilepsy onset and the longest duration of epilepsy. Across five time epochs, the diagnosis of AHS increased in the first epoch, remaining constant thereafter. Contrary to the trends in other pathologies, in the AHS group the mean age of patients at surgery increased by 7 years and the duration of epilepsy until surgery increased by 5 years. This trend could be replicated in all three centers. As initially hypothesized for all groups, age and duration of epilepsy in other pathology groups remained constant or indicated earlier submission to surgery. Conclusions During the first few years studied, most probably due to progress in brain imaging, the proportion of patients with AHS increased. However, despite stable numbers over time, and contrary to the trends in other pathology groups, age and duration of epilepsy in mesial TLE with AHS (mTLE + AHS) increased over time. This supports the hypothesis of a decreasing incidence of AHS. This trend is discussed with respect to disease‐modifying factors which have changed the incidence of classical mTLE + AHS or, alternatively, to recent developments in antiepileptic drug treatment, the appraisal of surgery and economic incentives for treatment options other than surgery.